IMPLEMENTASI KEARIFAN LOKAL BALI PADA TOPIK PERMASALAHAN LINGKUNGAN YANG MENGANCAM KEHIDUPAN DALAM PEMBELAJARAN IPS KELAS V SEKOLAH DASAR - Sudiartini, Ni Putu; I Wayan Lasmawan; I Wayan Kertih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to analyze the implementation of Balinese local wisdom in elementary schools on the topic of environmental problems that threaten life in social studies learning for grade V of SD N Gugus Ubud Bali. This type of research is a qualitative research, with a case study method. The population and sample of this study were teachers who teach grade V and all grade V students at SD Gugus Ubud Bali consisting of SDN 1 Ubud, SDN 2 Ubud, SDN 3 Ubud, SDN 4 Ubud, SDN 5 Ubud. The results of this study are Balinese local wisdom inserted into the topic of environmental problems that threaten life, namely the local wisdom of Tri Hita Karana, Subak, tumpek, and nangun sad kerti loka Bali. The conclusion of this study is the insertion of Balinese local wisdom in social studies learning to save the natural environment, namely Tri Hita Karana, subak, implementation of local wisdom tumpek and nangun sad kerti loka Bali. Activities carried out by students include planting trees, making hydroponics, and making ecobricks. It is recommended that further research can conduct experimental research to determine the influence of Balinese local wisdom with the integration of certain models and topics related to the natural environment to improve learning outcomes or environmental awareness at the elementary education level.